Genetic Architecture of Capitate Glandular Trichome Density in Florets of Domesticated Sunflower (Helianthus annuus L.) - Gao, Qing-Ming; Kane, Nolan C.; Hulke, Brent S.; Reinert, Stephan; Pogoda, Cloe S.; Tittes, Silas; Prasifka, Jarrad R. (Frontiers in Plant Science, 2018)
Capitate glandular trichomes (CGT), one type of glandular trichomes, are most common in Asteraceae species. CGT can produce various secondary metabolites such as sesquiterpene lactones (STLs) and provide durable resistance to insect pests. In sunflower, CGT-based host resistance is effective to combat the specialist pest, sunflower moth. However, the genetic basis of CGT density is not well understood in sunflower. In this study, we identified two major QTL controlling CGT density in sunflower florets by using a F4 mapping population derived from the cross HA 300 × RHA 464 with a genetic linkage map constructed from genotyping-by-sequencing data and composed of 2121 SNP markers. One major QTL is located on chromosome 5, which explained 11.61% of the observed phenotypic variation, and the second QTL is located on chromosome 6, which explained 14.06% of the observed phenotypic variation. The QTL effects and the association between CGT density and QTL support interval were confirmed in a validation population which included 39 sunflower inbred lines with diverse genetic backgrounds. We also identified two strong candidate genes in the QTL support intervals, and the functions of their orthologs in other plant species suggested their potential roles in regulating capitate glandular trichome density in sunflower. Our results provide valuable information to sunflower breeding community for developing host resistance to sunflower insect pests.